From TcVII to TcI; facile syntheses of bis-arene complexes [99(m)Tc(arene)2]+ from pertechnetate. Issue 1 (30th September 2014) - Benz, Michael; Braband, Henrik; Schmutz, Paul; Halter, Jonathan; Alberto, Roger
Abstract : Bis-arene complexes of technetium represent a fundamental class of organometallic compounds. Detailed insights into their properties are obtained due to novel and convenient synthetic routes. Abstract : Bis-arene complexes of technetium represent a fundamental class of organometallic compounds. Due to complex synthetic routes, no detailed insights into their properties have been reported so far. Reacting [ 99 TcO4 ] − with arenes in the exclusive presence of AlCl3 gives highly stable [ 99 Tc(arene)2 ] + in good yields. These complexes have extraordinarily high stabilities, where oxidation is found to occur at potentials higher than +1.3 V and reduction at potentials below −2 V vs. Fc/Fc + . The 99m Tc analogues are similarly synthesised by applying a novel ionic liquid extraction pathway. Complexes of 99m Tc with suitably functionalized arenes will represent new building blocks for bioorganometallic pharmaceuticals in molecular imaging.